VD_FINDINFO HC / 2014 / 581 vom 24. Juli 2014 - VD Tribunal cantonal (2014)
RETARD INJUSTIFIÉ, FORMALISME EXCESSIF, RECTIFICATIONEN GÉNÉRAL, RÉPONSEACTION EN JUSTICE | 132 al. 1 CPC (CH), 221 CPC (CH), 222 al. 2 CPC (CH), 319 let. b ch. 2 CPC (CH), 319 let. c CPC (CH)